2012
DOI: 10.4062/biomolther.2012.20.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HIF-1α by Valproic Acid Sustains Self-Renewal of Mouse Embryonic Stem Cells under Hypoxia In Vitro

Abstract: The developing embryo naturally experiences relatively low oxygen conditions in vivo. Under in vitro hypoxia, mouse embryonic stem cells (mESCs) lose their self-renewal activity and display an early differentiated morphology mediated by the hypoxia-inducible factor-1α (HIF-1α). Previously, we demonstrated that histone deacetylase (HDAC) is activated by hypoxia and increases the protein stability and transcriptional activity of HIF-1α in many human cancer cells. Furthermore HDAC1 and 3 mediate the differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, it is well documented that HDACs and histone methyltransferases possess compensatory functions 26 . Therefore we used the pan-HDAC inhibitor valproic acid (VPA) 27 , which enhanced histone H3 acetylation in MCF7 cells in vitro ( Fig. 2e ), and significantly increased LIFR and SOCS3 mRNA levels in hypoxia ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is well documented that HDACs and histone methyltransferases possess compensatory functions 26 . Therefore we used the pan-HDAC inhibitor valproic acid (VPA) 27 , which enhanced histone H3 acetylation in MCF7 cells in vitro ( Fig. 2e ), and significantly increased LIFR and SOCS3 mRNA levels in hypoxia ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a study has reported that hypoxia is not beneficial for maintaining human embryonic stem cells in the undifferentiated state [ 39 ]. Another study has demonstrated that mouse embryonic stem cells lose self-renewal activity under in vitro hypoxia [ 40 ]. Our present results showed that hypoxia exposure reduced the expression of SIX-2 and CITED1 and the number of SIX-2-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs also participate in the regulation of stemness property of normal stem cells. HDAC1 and HDAC3 were shown to be activated by hypoxia and mediate the differentiation of mouse embryonic stem cells and hematopoietic stem cells [ 65 ]. Octamer-binding transcription factor 4 (Oct4) is an important transcriptional factor of embryonic stem cells which is commonly used as a marker of normal stem cells and cancer stem-like cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, another HDACI valproic acid (VPA) was previously reported to enhance self-renewal and cytokine-induced expansion of hematopoietic stem cells [ 96 98 ]. VPA could maintain the self-renewal ability of mouse embryonic stem cells (mESCs) under hypoxic conditions by suppression of HIF-1alpha [ 65 ]. Conversely, in a recent study, VPA induced significant upregulation of neuroprogenitor marker Musashi, CD133 and Nestin, which suggests that VPA may play a key role in neuronal differentiation of human bone-marrow mesenchymal stromal cells (BM-MSCs) [ 99 ].…”
Section: Introductionmentioning
confidence: 99%